2019
DOI: 10.1029/2018wr023034
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Dynamic Nonequilibrium Effects in Drainage Processes of an Air‐Water Two‐Phase Fine Sandy Medium

Abstract: In efforts to reduce uncertainties about effects of minor changes in the pore structure of porous media on dynamic nonequilibrium effects (DNEs), we monitored water saturation‐capillary pressure relationships in both dynamic flow and static states in stepwise drainage processes of a sandy medium. The acquired data were used to detect DNE and their changes with time in each drainage step and construct new parameters to characterize DNE. Effects of factors affecting water flow—including capillary number, water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…As can be seen, both the values of d decreases monotonically with increasing dSw/dt for drainage processes (Camps-Roach et al, 2010;Li et al, 2019;Sakaki et al, 2010). However, in our experiments,  first decreases and then increases as the fluctuation period decreases for both drying and wetting (Figures 10a,c).…”
Section: Values Of Fitting Parameters and Air-entry Pressuresupporting
confidence: 52%
See 3 more Smart Citations
“…As can be seen, both the values of d decreases monotonically with increasing dSw/dt for drainage processes (Camps-Roach et al, 2010;Li et al, 2019;Sakaki et al, 2010). However, in our experiments,  first decreases and then increases as the fluctuation period decreases for both drying and wetting (Figures 10a,c).…”
Section: Values Of Fitting Parameters and Air-entry Pressuresupporting
confidence: 52%
“…Note that the trend of air-entry pressure is consistent with  since the air-entry pressure is inversely proportional to  . Li et al (2019) observed an increasing air-entry pressure with increasing flow velocity. This is because the maximum flow rate in their experiments was 2.59 × 10 -4 m/s, two orders of magnitude smaller than the average fluctuation rate of 1.9 × 10 -2 m/s in our experiment with amplitude of 0.19 m and period of 4000 s. Thus, the pore water blockage may not occur in their experiments.…”
Section: Values Of Fitting Parameters and Air-entry Pressurementioning
confidence: 88%
See 2 more Smart Citations
“…Traditionally, the WRC has been considered a stationary or equilibrium relationship. The transient, or dynamic WRC, evolving from fast changes in suction or prescribed flow with high flow rates, has been investigated amongst others by Topp et al [46], Hassanizadeh et al [14], Zhuang [53], Milatz et al [30] and Li et al [22]. Independent findings show that different water retention curves are obtained for different rates of pore water volume change oV w ot or depending on the change rate of degree of saturation with time oS r ot .…”
Section: The Importance Of Water Retention Behaviourmentioning
confidence: 99%